2022
DOI: 10.3897/compcytogen.v16.i3.90336
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype and COI gene sequences of Chironomus melanotus Keyl, 1961 from the Yaroslavl region, Russia, and the difficulties with its identification using GenBank and BOLD systems

Abstract: Karyotype and COI gene sequences of Chironomus melanotus Keyl, 1961 from the Yaroslavl region (Russia) were analyzed. A low level of chromosomal polymorphism has been confirmed, eventually eight banding sequences were found: melA1, melB1, melC1, melD1, melE1, melF1, and melG1; only melD2 was found in two larvae from the Sunoga river. Analysis of phylogenetic tree and estimated genetic distances has shown not all COI gene sequences of Ch. melanotus in GenBank and BOLD to belong to this species. The lower distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, we used COI gene sequences of Ch. "annularius" from the GenBank and BOLD databases, realizing that there may be errors in species identification, as mentioned earlier [25,27].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, we used COI gene sequences of Ch. "annularius" from the GenBank and BOLD databases, realizing that there may be errors in species identification, as mentioned earlier [25,27].…”
Section: Discussionmentioning
confidence: 96%
“…The Chironomus species have giant polytene chromosomes with which we usually can accurately identify their species [7,12,23,24]. We already know that for the best results in identifying the species of chironomids, it is necessary to use a comprehensive approach that includes morphological, cytogenetic, and molecular genetic analyses [25][26][27].…”
Section: And Kiknadzementioning
confidence: 99%
“…Unfortunately, we did not have the opportunity to collect more samples of this species. We regularly suggest to use a comprehensive approach to the species identification of the genus Chironomus , which includes morphology, cytogenetics and molecular genetics ( Bolshakov and Movergoz 2022 ; Bolshakov et al 2022a , 2022b ). In this study, we have decided to use a single Chironomus larva to obtain a complex of scientific data.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of molecular genetic analysis further supported the suggestion that both species belong to the Ch. plumosus group ( Djomin 2011 ; Karmokov 2019 ; Bolshakov and Movergoz 2022 ; Bolshakov et al 2022a ) so both species are now considered members of the Ch. plumosus group.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that the species name "Chironomus melanotus" matches several COI gene sequences, and the genetic p-distance between different populations varied from 0.4 to 12.4%, indicating that not all sequences belong to Ch. melanotus [11]. As we know, the genetic distance threshold is not suitable for all Chironomus species and depends on intra and interspecific sequence divergences; for the COI gene, it varies from 9 to 20% and, in rare cases, from 1 to 4% [12].…”
Section: Introductionmentioning
confidence: 99%